Performance analysis of Medicinal Kaempferia species - Akoijam Ranjita Devi (Department of Plantation Crops and Spices, College of Horticulture, 2019)
The medicinal Kaempferia species are a good source of valuable bioactive compounds. Kaempferia rotunda is widely used in the ancient systems of medicine in India and Indonesia. Kaempferia parviflora, popularly known as black ginger or Thai ginseng, has potential for great exploitation on commercial basis. Rhizomes of K. parviflora are used as aphrodisiac in traditional medicine in Thailand. The present study was undertaken at Department of Plantation crops and Spices, Kerala Agricultural University, Thrissur to evaluate the medicinal Kaempferia species in terms of morphology, anatomy, floral biology, yield, medicinal as well as pharmacological properties. A total of 18 genotypes belonging to three different species of Kaempferia formed the material for the study. Kaempferia galanga was taken as a reference species. The morphological evaluation was done consecutively for two years (2017-18 and 2018-19) based on qualitative and quantitative parameters. In K. rotunda, there was not much variation in qualitative parameters while the quantitative parameters exhibited tremendous variation among the 13 genotypes evaluated. The fresh rhizome yield ranged from 15.21 to 52.44 g/plant and dry yield of rhizome ranged from 5.00 to 17.73 g/plant. The Manipur collection MCR-6 performed best with the highest fresh as well as dry rhizome yield of 52.44 g and 17.73 g respectively followed by KCR-5 from Kerala. In K. parviflora also, the qualitative parameters did not show much variation whereas the quantitative characters exhibited significant variation among the genotypes. Significantly highest (114.60 g) fresh weight of rhizome was recorded by the genotype KCP-1. The Thailand collection KCP-1 was the best performer followed by BSI-1 from Shillong. The two genotypes of K. galanga evaluated in the study exhibited morphological variation in certain characters, however no significant variation was noticed for rhizome yield. The flowering was observed from May to November in K. parviflora, March to April in K. rotunda and June to July in K. galanga. In the floral biology studies, variation was noticed in floral parts including the pollen grains of the three species with respect to size and shape. The flowers were bisexual, complete, trimerous and zygomorphic in all the species. There were on an average 14.2 number of flowers per inflorescence in K. parviflora, 8.9 flowers in K. rotunda and 5.6 flowers per inflorescence in K. galanga. The time of anthesis was 5.00 am to 7.15 am in K. parviflora, 4.00 to 5.00 am in K. rotunda and in case of K. galanga, peak anthesis time was 4.00 to 5.00 am. The stigma was receptive upto eight hours after the anthesis in K. parviflora whereas K. rotunda and K. galanga remained receptive for 24 hours and nine hours respectively after anthesis. In the in vivo pollen germination studies, pollen germination was noticed only in K. parviflora and K. galanga. The seed set was observed only in K. parviflora. The vivipary was observed in K. parviflora and recalcitrance of the seed was confirmed, thus proving its viviparous nature. The viviparous plants were compared with rhizome borne plants. The number of leaves and tillers were more in viviparous plants when compared with normal plants but they took two years for appreciable yield. However, rhizome yield of viviparous plant was only 1/3rd of that in normal plants. In the anatomical studies, all the three species had collateral and closed type of vascular bundles in transverse section of leaves. The oil globules were present in the leaf lamina of K. galanga. Calcium oxalate crystals were present in the leaf epidermis of K. rotunda and leaf lamina in K. parviflora. Oil globules were abundant in the rhizome of K. rotunda and K. parviflora. Starch granules in rhizome and root tuber were concentrated near endodermal layer in all the species. The flavonoid vacuoles were abundantly present in the rhizome section of K. parviflora. In the biochemical studies, the volatile oil content in K. rotunda rhizome ranged from 0.057 to 3.17 per cent and oleoresin content was to the tune of 0.60 to 3.17 per cent. In K. parviflora, volatile oil content was negligible; oleoresin content ranged 2.03 to 4.17 per cent. The content of starch, total sugars and flavonoids were high in K. parviflora whereas total free amino acid content was high in K. rotunda rhizome. The profiling of volatile oil of K. rotunda by GCMSMS detected 22 compounds, that of K. parviflora indicated 34 compounds and in K. galanga there were 27 compounds. The profiling of ethanolic extract of K. rotunda rhizome by GCMS showed the presence of 18 compounds and that of K. parviflora, eight compounds. The ethanolic extract of rhizome of K. rotunda and K. parviflora were subjected to detailed in vitro as well as in vivo pharmacological studies at the Dept. of Pharmacology and Toxicology, KVASU, Mannuthy. The in vivo acute toxicity and immunomodulatory study was carried out in Swiss albino mice using cyclophosphamide as immunosuppressive agent. No acute toxicity was noticed in the ethanolic extract of both K. rotunda and K. parviflora. Both the species significantly increased the body weight, total leukocyte count, serum protein and decreased neutrophil count in normal as well as immunosuppressed animals. A significant stimulation of humoral and cellular immune response was indicated by increase in antibody titre, bone marrow cellularity and DTH reaction. Histopathology of spleen confirmed the high immunomodulatory effect of K. parviflora and moderate immunomodulatory activity of K. rotunda. In the DPPH assay, K. rotunda exhibited high antioxidant activity (IC50 131.15 μg/ml) while K. parviflora showed lower activity (IC50 198.68±7.62 μg/ml). Ethanolic rhizome extract of both the species exhibited anticancer property in breast cancer cell lines. Both K. rotunda and K. parviflora showed cytotoxicity against MDA MB231 and MCF-7 cell lines. IC50 for K. rotunda was 167.1±5.60 and 194.8±8.97 respectively for MCF-7 and MDA MB231 cell lines while for K. parviflora it was 143.03±2.70 and 126.35±2.53 respectively. The ethanolic extract of K. rotunda and K. parviflora exhibited appreciable antimicrobial activity on E. coli (11.13±0.16 mm, 12.32±0.12 mm), S. enterica (11.47±0.29 mm, 13.8±0.16 mm) and P. aeruginosa (11.52±0.38 mm, 11.17±0.31 mm) and showed potent activity on S. aureus (14.18±0.32 mm, 15.48±0.23 mm).